Portal do professor e educação física adaptada: sugestões para a prática docente inclusiva - Bataliotti, Soellyn Elene (2013)
The Teacher's Portal (Portal do Professor) is an educational repository launched by a partnership between the Ministry of Education, Ministry of Science and Technology, linked to the Distance Education Secretary, which aims to offer resources that collaborate with the pedagogical practice of teachers around the country. Among the possibilities that this repository provides, there is the category "Class Space" where it is possible to find suggestions of lessons for the Physical Education discipline with planning focused on special and inclusive education. The practice of working with the discipline of Physical Education for special education will be entitled, in this study, "Adapted Physical Education". To understand the need for lessons planning toward inclusive practice is important to know the history of Adapted Physical Education as well as Special and Inclusive Education in Brazil, which allowed the deployment of Multifunctional Resource Rooms, creating opportunities for the participation of the students to complement and supplement the education proposed by the school. Therefore, this research attempts to answer how the suggestions of Adapted Physical Education classes, proposed in the Teacher's Portal, can subsidize the practice of inclusive education in Physical Education classes and if it also allows the supplementary teaching in the Multifunctional Resource Rooms. To answer this question, the general objective will be to analyze the lesson plans available in the Teacher's Portal and its applicability to the classes of Physical Education with groups of inclusion. Thus, to reach the objective, this study conducted an investigation through exploratory and participant research, due to the fact that this theme is still not widely explored and to the investigations performed by the researcher during the study. The applications of the suggestions of Adapted Physical Education classes were held in a classroom of the 2nd year of Elementary School, through the additional resource of the proposal in the Multifunctional Resource Room attendance. For the data collection and analysis, the content analysis was used, in three steps: Observation, Planning and Intervention. During the three moments of this survey, it was possible to find data in order to achieve the proposed objectives and to conclude that the Teacher s Portal may collaborate with suggestions for lessons that subsidize the practice of the Physical education teacher; however, it is necessary to study the suggestion and the adaptation to the teacher s and the students reality for classes. For the attendance in the Multifunctional Resource Rooms, the use of indicated resources listed under "additional resources", contained in the lesson s suggestion of the Teacher's Portal, must be articulated with the students needs, with the content worked by the teacher in the common room and by the Physical Education teacher.